Temporal analysis of thyroid cancer management in a Melbourne tertiary centre. Issue 1 (18th October 2016) - Lee, James C.; Chang, Paula; Grodski, Simon; Yeung, Meei; Johnson, William; Serpell, Jonathan
Abstract : Background: The American Thyroid Association (ATA) management guidelines for thyroid cancer were revised in 2009. The aim of this study was to determine if management of thyroid cancer in our institution has changed in accordance with the introduction of the revised ATA guidelines (ATA 2009 ), and to compare the characteristics and management of thyroid cancer in a Melbourne endocrine surgery unit over a 7‐year period. Methods: All patients treated by the Monash University Endocrine Surgery Unit for thyroid cancer between 2007 and 2013 were divided into two groups – the pre‐ATA 2009 group (2007–2010) and the post‐ATA 2009 group (2011–2013). Comparisons were made of the demographics, cytology, pathology, surgical outcome and adjuvant therapy using t ‐test and chi‐squared tests. Results: There were 333 patients in the pre‐ATA 2009 group and 342 patients in the post‐ATA 2009 group. Fewer non‐diagnostic fine‐needle aspiration cytology results were identified in the post‐ATA 2009 group (4% versus 0.9%; P = 0.01), while the rates of other fine‐needle aspiration cytology categories were similar. There was a reduction in the use of radioactive iodine ablation in the post‐ATA 2009 group, both in the proportion of patients being treated (66% versus 48%; P < 0.001) and the dosages used (mean 96 mCi versus 80 mCi; P < 0.01), despite similar tumour size in both groups. Conclusion: The key changes in practice thought to be attributable to the 2009 revised ATA guidelines were the reduction in the use and dosage of radioactive iodine in the management of differentiated thyroid cancer.